Absence of Secondary Legislation in the Recognition of Nature as a Subject of Rights in Ecuador - Macharé Pincay, Oswaldo; Alcívar Toala, Mallury Elizabeth; Andraus Quintero, Cesar Enrique (Ius Humani. Jornal do direito, 2024)
The present study carries out a scientific review on the implementation of the rights of nature, enshrined in the Constitution of the Republic of Ecuador of 2008, a pioneering document worldwide for recognizing nature as a subject of rights. Despite this legal advance, the lack of secondary regulations has prevented its effective materialization, constituting the main objective of this research. Through a qualitative approach, the specialized doctrine and existing regulations were analyzed and synthesized, making it evident that the declaration of nature as a subject of rights is a milestone in both the national and international legal sphere. Likewise, it is highlighted that the political decision of the Ecuadorian State has been positively valued at a global level, establishing the bases for future actions focused on the care of Pachamama. The findings show the need to develop and apply secondary regulations that facilitate the practical application of these rights, ensuring the effective protection of nature.